(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Every gram of soil has a profusion of microbial cells, and the tissues of plants and animals are replete with microorganisms. In light of current findings on microbiomes, the mechanisms mediated by microbes in the regulation of physiological processes of their hosts have been thoroughly examined. The elements that make up these microbiomes can organize into different communities in plants, such as those living in the phyllosphere, endosphere, and rhizosphere. The "microbial tissue" in each of these niches is determined by and reacts to particular selective forces. The entire function of the plant microbiome is unclear, although there is strong evidence that these communities influence stress tolerance, improve nutrient uptake, and regulate disease. The features of the microbial communities that make up the plant microbiome are first outlined in this review, and then we give a number of research that explain the underlying mechanisms that shape the functional and phylogenetic communities associated with plants. We support the hypothesis that a better understanding of the processes through which plants interact and choose their microbiomes may directly impact plant growth and health. It may also pave the way for the development of novel microbiome-driven strategies that can effectively address the demands of a more sustainable agricultural sector.